Benign intramural gastric tumors - Farcic, Antonio; Schneeberger, Federico; Iraola, María L (Cirugía del Uruguay, 1978)
Case ,material consists o'f a series of 20 benign intramural gastric tumors, found in different surgical centres in MÓ